A versatile source of single photons for quantum information processing - Förtsch, Michael; Fürst, Josef; Wittmann, Christoffer; Strekalov, Dmitry; Aiello, Andrea; Chekhova, Maria V.; Leuchs, Gerd; Silberhorn, Christine; Marquardt, Christoph (Nature Communications, 2013)
The generation of high-quality single-photon states with controllable narrow spectral bandwidths and central frequencies is key to facilitate efficient coupling of any atomic system to non-classical light fields. Such an interaction is essential in numerous experiments for fundamental science and applications in quantum communication and information processing, as well as in quantum metrology. Here we implement a fully tunable, narrow-band and efficient single-photon source based on a whispering gallery mode resonator. Our disk-shaped, monolithic and intrinsically stable resonator is made of lithium niobate and supports a cavity-assisted spontaneous parametric down-conversion process. The generated photon pairs are emitted into two highly tunable resonator modes. We verify wavelength tuning over 100 nm of both modes with controllable bandwidth between 7.2 and 13 MHz. Heralding of single photons yields anti-bunching with g (2) (0)<0.2. © 2013 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2022-06-05

Interfacing transitions of different alkali atoms and telecom bands using one narrowband photon pair source - Schunk, Gerhard; Vogl, Ulrich; Strekalov, Dmitry V.; Förtsch, Michael; Sedlmeir, Florian; Schwefel, Harald; Göbelt, Manuela; Christiansen, Silke; Leuchs, Gerd; Marquardt, Christoph (Optica, 2015)
Quantum information technology strongly relies on the coupling of optical photons with narrowband quantum systems, such as quantum dots, color centers, and atomic systems. This coupling requires matching the optical wavelength and bandwidth to the desired system, which presents a considerable problem for most available sources of quantum light. Here we demonstrate the coupling of alkali dipole transitions with a tunable source of photon pairs. Our source is based on spontaneous parametric downconversion in a triply resonant whispering gallery mode resonator. For this, we have developed novel wavelength-tuning mechanisms that allow a coarse tuning to either the cesium or rubidium wavelength, with subsequent continuous fine-tuning to the desired transition. As a demonstration of the functionality of the source, we performed a heralded single-photon measurement of the atomic decay. We present a major advance in controlling the spontaneous downconversion process, which makes our bright source of heralded single photons now compatible with a plethora of narrowband resonant system
Keywords: Atomic; Quantum communications; Quantum optics; Spectroscopy

Nonlinear optics in crystalline: Whispering gallery resonators - Marquardt, Christoph; Strekalov, Dmitry V.; Fürst, Josef; Förtsch, Michael; Leuchs, Gerd (Optics and Photonics News, 2013)
CRIS-Team Scopus Importer:2022-06-05

Novel sources for polarisation squeezing and polarisation entanglement using photonic crystal fibres - Milanovic, Josip; Lassen, Mikael; Förtsch, Michael; Marquardt, Christoph; Andersen, Ulrik Lund; Leuchs, Gerd (CLEO/Europe - EQEC 2009 - European Conference on Lasers and Electro-Optics and the European Quantum Electronics Conference, 2009)
CRIS-Team Scopus Importer:2022-06-05